Rola i pozycja kobiety w staropolskich ekonomikach = Woman's role and position in Old-Polish books - Korczyńska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article investigates the role and position of a woman in Sarmatian culture, which is one of the most characteristic periods in Polish history. Those days it was assumed that Polish gentry stems from an Ancient brave Sarmatian people. A real Old-Polish noblemen was a devoted Catholic who strongly propagated family and social ties. However, how was an ideal Sarmatian woman depicted?
Keywords: kobieta; książka